Enhancing farmers' land productivity through sustainable palm oil certification: Strategies for promoting environmental and economic benefits in agricultural practices - Rahutomo, Andreas Budi; Karuniasa, Mahawan; Frimawaty, Evi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: With more than 40% of Indonesia's oil palm land under its management, smallholders still face challenges on the low land productivity and certification achievement. Methods: This research aims to develop a certification concept capable to increase the smallholders’ land productivity through descriptive statistics, grounded theory, content analysis, and Analytic Hiearachy Process. Findings: This research finds that ISPO and RSPO certified smallholders achieved 82% higher land productivity than the average conventional ones, in line with their compliance with certification and consistent GAP application. Fertilisation needs to be prioritised to increase productivity, with the GAP Application and Monitoring (RSPO) and Plant Maintenance (ISPO) as the supporting certification criteria. Conclusion: Synergy between ISPO and RSPO has a chance to increasing land productivity through certification compliance, hence accelerating smallholder certification achievement which would reduce deforestation rates from oil palm expansion. Novelty/Originality of this article: This study introduces a certification concept that combines ISPO and RSPO standards to enhance smallholder land productivity. It emphasizes the integration of fertilization, GAP application, and plant maintenance as key components for boosting productivity while ensuring certification compliance, offering a novel approach to reducing deforestation rates in Indonesia's oil palm sector.